Ipriflavone Suppresses Growth of Esophageal Squamous Cell Carcinoma Through Inhibiting mTOR In Vitro and In Vivo - Shi, Xiaodan; Zhang, Yuanyuan; Xie, Xiaomeng; Pang, Mengjun; Laster, Kyle; Li, Jian; Ma, Xinli; Liu, Kangdong; Dong, Zigang; Kim, Dong Joon (Frontiers in Oncology, 2021)
Ipriflavone, a synthetic isoflavone that inhibits osteoclastic bone resorption, has been used clinically for the treatment of osteoporosis. However, the anticancer activity of Ipriflavone and its molecular mechanisms in the context of esophageal squamous cell carcinoma (ESCC) have not been investigated. In this study, we report that Ipriflavone is a novel mammalian target of rapamycin (mTOR) inhibitor that suppresses cell proliferation and induces cell apoptosis in ESCC cells. Ipriflavone inhibited anchorage-dependent and -independent growth of ESCC cells. Ipriflavone induced G1 phase cell cycle arrest and intrinsic cell apoptosis by activating caspase 3 and increasing the expression of cytochrome c. Based on the results of in vitro screening and cell-based assays, Ipriflavone inhibited mTOR signaling pathway through directly targeting mTOR. Knockdown of mTOR strongly inhibited the growth of ESCC cells, and the cell growth inhibitory effect exerted by Ipriflavone was found to be dependent upon mTOR signaling pathway. Remarkably, Ipriflavone strongly inhibited ESCC patient-derived xenograft tumor growth in an in vivo mouse model. Our findings suggest that Ipriflavone is an mTOR inhibitor that could be potentially useful for treating ESCC.